Release film and method for producing same

By using a specific mold release film in the filming process of ceramic green sheets, the problems of insufficient light peelability and insufficient wetting properties are solved, and the uniform thickness and efficient peeling of ceramic green sheets are achieved, reducing the burden on the human body and the environment.

CN119866269APending Publication Date: 2025-04-22TOYOBO CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380065814.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-12
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing mold release films have problems such as insufficient light peelability and insufficient wetting properties during the filming process of ceramic green sheets, resulting in defects such as uneven coating, shrinkage and uneven thickness, which affects the yield rate of laminated ceramic capacitors.

Method used

A release film with a specific structure is used, which consists of a polyester film and a release layer formed by reaction and solidification by aqueous coating composition. The aqueous coating composition contains 10 parts by mass or less of organic solvent, including an alkenyl-rich silicone emulsion, a hydrogen-rich silicone emulsion and a surfactant. The release layer is formed by an online coating method, and heat treatment is performed at high temperature to complete the crystallization orientation.

Benefits of technology

The peeling and wetting properties of the mold release layer are improved, the defects of ceramic green sheets are generated, and the harmful effects on the human body and the environment are reduced. There is no need for explosion-proof drying equipment, and energy consumption is reduced and CO2 emissions are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005309744500000171
    Figure BDA0005309744500000171
  • Figure BDA0005309744500000181
    Figure BDA0005309744500000181
  • Figure BDA0005309744500000311
    Figure BDA0005309744500000311
Patent Text Reader

Abstract

Provided are: a mold release film which is capable of reducing organic solvents that are harmful to the human body and adversely affect the environment, and which has good wettability and lightly peelable properties of a thin resin sheet, particularly a thin ceramic green sheet; and a method for producing the mold release film. The present invention relates to a mold release film having a mold release layer on at least one surface of a polyester film, and a method for producing the same, the mold release layer being a layer obtained by reacting and solidifying an aqueous coating composition, the aqueous coating composition containing 10 parts by mass or less of an organic solvent per 100 parts by mass of the total amount of the coating composition, the composition contains (a) a first silicone emulsion containing at least two or more alkenyl groups in one molecule, (b) a second silicone emulsion containing at least two or more hydrogen groups in one molecule, and (d) a surfactant. The adhesion energy of the surface of the release layer, calculated from the rolling angle of water, is 6.0 mJ / m2 or more, and the tape release force is 2000 mN / 50 mm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a release film having a base film and a release layer and a method for producing the same, and also relates to a release film useful as a film for various processes and a method for producing the same. Background Art

[0002] In the past, a release film having a release layer laminated on a polyester film or the like as a substrate has high heat resistance and mechanical properties and is used as a process film for forming resin sheets such as adhesive sheets, cover films, ceramic green sheets, and polymer electrolyte membranes. In addition, as a release layer of a release film, since it has good heat resistance and peelability, a variety of release layers formed by coating compositions containing silicone have been proposed (e.g., Patent Documents 1 to 5).

[0003] The aforementioned release film is also used as a process film for forming ceramic green sheets that require high smoothness, such as laminated ceramic capacitors and ceramic substrates. In recent years, along with the miniaturization and high capacity of laminated ceramic capacitors, the thickness of ceramic green sheets has also tended to be thinner. Ceramic green sheets are formed by coating a slurry containing ceramic components such as barium titanate and an adhesive resin on the release layer of a release film and drying it. Electrodes are printed on the formed ceramic green sheets, and ceramic green sheets with electrodes are obtained by peeling them off from the release film. The obtained ceramic green sheets with electrodes are stacked, pressed, fired, and coated with external electrodes, thereby manufacturing laminated ceramic capacitors.

[0004] Patent documents 1 and 2 propose a release film which is produced by the following method (hereinafter referred to as "off-line coating"): a coating composition comprising a polysiloxane having an unsaturated group, a polysiloxane having an Si-H group, a platinum group metal catalyst, and an organic solvent is applied to one side of a biaxially stretched polyester, and the coating composition is dried and cured by heat treatment to form a release layer.

[0005] Patent document 3 proposes a release film, which forms a release layer by the following method (hereinafter referred to as "in-line coating"): an aqueous coating composition containing olefin-containing silicone and Si-H-containing silicone is coated on one side of a polyester film, and then the polyester film is stretched.

[0006] In addition, a release film using off-line coating is proposed in Patent Document 4. Furthermore, a release film using in-line coating is proposed in Patent Document 5.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 2003-292894

[0010] Patent Document 2: WO2017 / 200056

[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 2010-17932

[0012] Patent Document 4: Japanese Patent No. 6619200

[0013] Patent Document 5: Japanese Patent Application Laid-Open No. 2021-11081 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] In recent years, along with the thin filmization of ceramic green sheets, there is a tendency to require a release film that can peel off the ceramic green sheets with a low and uniform force. In addition, a release film with good wettability to the ceramic slurry coated on the release layer is required. In order to thin the ceramic green sheets, for example, it is required to use an organic solvent in an amount greater than the amount of resin, and evenly apply the diluted ceramic slurry with a low solid content concentration on the release layer. If a ceramic slurry containing such a composition is applied to the release layer, the wettability of the release film to the ceramic slurry sometimes becomes insufficient, and a small amount of shrinkage cavities and uneven coating occur during coating, thereby causing concerns about pinholes and uneven thickness on the ceramic green sheets, and concerns about deterioration in the yield of stacked ceramic capacitors.

[0016] As a result of intensive studies, the present inventors have found that, in a release layer formed by applying an aqueous coating composition and then reacting and solidifying it, an organic solvent contained in the composition also affects the physical properties of the release layer.

[0017] Specifically, there are problems such as the organic solvent impairing the stability of the aqueous dispersion contained in the aqueous coating composition, impairing the uniformity of the release layer formed from the composition, and deteriorating the releasability.

[0018] In addition, there is a problem that the amount of the organic solvent used increases, which leads to increased toxicity to the human body and increased environmental burden.

[0019] Patent Documents 1 and 2 particularly require that the thin ceramic green sheet have both easy peelability and good wettability. In addition, since a coating composition containing an organic solvent as a main component is used, the adverse effects on the human body caused by contact with the organic solvent and inhalation of vapor, and the burden on the global environment caused by the release of organic solvent vapor into the atmosphere have become problems.

[0020] In addition, since the drying equipment for organic solvents must be explosion-proof equipment, it requires initial installation costs and requires a large amount of energy for operation, resulting in a large amount of CO2 emissions and a heavy environmental burden.

[0021] In Patent Document 3, a release layer is formed by using a coating composition of a mixed solvent of water and isopropyl alcohol, but this has problems of being harmful to the human body and having a great environmental burden.

[0022] In addition, alcohol solvents such as isopropyl alcohol have the following problems: the stability of the water-dispersed emulsion is impaired, the coating uniformity is impaired due to the aggregation and gelation of the emulsion, and coating defects such as coarse protrusions and shrinkage holes caused by the aggregates occur. In particular, when forming a release layer using silicone with excellent releasability, silicone must be emulsified because silicone is generally insoluble in water, which has become a problem in the production of a release film that exhibits easy releasability.

[0023] Since the release film described in Patent Document 4 contains an organic solvent as a main component in the composition forming the release layer, it has the problems of being harmful to the human body and having a large environmental burden as described above. In addition, the biaxially stretched polyester film as a substrate has a concern of being deformed by the heat during drying and curing of the coating composition, and must be produced at a low temperature.

[0024] In the invention of Patent Document 4, as described in the examples, the coating composition is cured by heat at 135° C., and there is a concern that the heat for curing the release layer may be insufficient. If the release layer is insufficiently cured, the solvent resistance of the release layer may be impaired, the force for peeling the ceramic green sheet may increase, and the ceramic green sheet may be damaged during peeling, causing defects.

[0025] Since the release film described in Patent Document 5 uses an aqueous coating composition, there is a concern that coating defects such as shrinkage holes may occur during the drying process when the aqueous coating composition is applied to the polyester film. In addition, since a water-dispersed emulsion is used, there is a concern that the emulsion is destroyed due to shear and heat during coating, and gelled products and aggregates are mixed into the release layer, causing coating defects such as uneven thickness of the release layer, the generation of coarse protrusions, and coating omissions. There is a concern that these coating appearances may have an adverse effect on the releasability of the ceramic raw sheet. In addition, in-line coating must be manufactured at a relatively high temperature for the stretching and orientation crystallization of the polyester film. Therefore, compared with offline coating, the release layer is easy to cure and becomes a release layer with excellent releasability, but there is a concern that the wettability of the ceramic slurry may become insufficient.

[0026] The present invention was completed against the background of the problems in the prior art. That is, the purpose is to provide a release film and a method for producing the same, wherein the release film can reduce organic solvents that are harmful to the human body and have adverse effects on the environment, and has both easy release properties and good wettability for thin resin sheets, especially thin ceramic green sheets.

[0027] Solutions for solving problems

[0028] The present inventors have conducted intensive studies to solve the above problems and have found that the above objects can be achieved by a release film having the following structure and a method for producing the same, thereby completing the present invention.

[0029] That is, the present invention is formed by the following configurations.

[0030] [1] A release film comprising a polyester film and a release layer in this order,

[0031] The release layer is a layer formed by reacting and solidifying the aqueous coating composition.

[0032] The aqueous coating composition contains 10 parts by mass or less of an organic solvent relative to 100 parts by mass of the total amount of the aqueous coating composition;

[0033] The aqueous coating composition comprises:

[0034] (a) a first silicone emulsion containing at least two alkenyl groups in one molecule,

[0035] (b) a second silicone emulsion containing at least two hydrogen groups in one molecule, and

[0036] (d) a surfactant,

[0037] In the aforementioned release layer,

[0038] The adhesion energy of the surface of the release layer calculated from the rolling angle of water was 6.0 mJ / m 2 above,

[0039] The tape peeling force measured by the following method is less than 2000mN / 50mm;

[0040] The release film was immersed in toluene for 15 minutes and then air-dried. Then, an adhesive tape was attached to the release layer and pressed with a load of 5 kg. The release film with the tape was kept at 70°C for 20 hours and then T-peeled at a peeling speed of 0.3 m / min to measure the peeling force of the tape.

[0041] [2] The release film according to [1], wherein the aqueous coating composition contains:

[0042] (c) Containing SiO 4 / 2 It represents an aqueous dispersion of a silicone with Q unit.

[0043] [3] The release film according to [1] or [2], wherein in the aqueous coating composition,

[0044] (a) the number average molecular weight of the first silicone emulsion containing at least two alkenyl groups in one molecule is 1,000 or more and less than 30,000;

[0045] (b) The second silicone emulsion containing at least two hydrogen groups in one molecule has a number average molecular weight of 1,000 to 10,000.

[0046] [4] A release film according to any one of [1] to [3], wherein the release film is formed by the following steps: coating the aqueous coating composition on a substrate film before the substrate film has been crystalline oriented, stretching the substrate film in at least one direction, and heat treating the substrate film to complete the crystalline orientation of the substrate film.

[0047] [5] The release film according to any one of [1] to [4], wherein the polyester film has a surface layer substantially free of inorganic particles, and the release layer is formed on the surface layer.

[0048] [6] The release film according to any one of [1] to [5], wherein the release film is a release film for producing a laminated ceramic capacitor or a resin sheet.

[0049] [7] A method for producing a release film or the method for producing a release film according to any one of [1] to [6], comprising the following steps:

[0050] a coating step of coating the aqueous coating composition on at least one side of the polyester film, and

[0051] a heating step of heating the polyester film coated with the aqueous coating composition;

[0052] In the coating step, the aqueous coating composition contains 10 parts by mass or less of an organic solvent relative to 100 parts by mass of the total amount of the aqueous coating composition.

[0053] The aqueous coating composition contains water, a water-soluble component and / or a water-dispersible emulsion.

[0054] The surface tension of the aqueous coating composition is 40 mN / m or less.

[0055] [8] The method for producing a release film according to [7], comprising the coating step of using the aqueous coating composition,

[0056] The aqueous coating composition comprises:

[0057] (A) a first silicone emulsion containing at least two alkenyl groups in one molecule,

[0058] (B) a second silicone emulsion containing at least two hydrogen groups in one molecule, and

[0059] (D) a surfactant,

[0060] The boiling point of the surfactant is 200° C. or higher.

[0061] [9] The method for producing a release film according to [7] or [8], wherein the heating step comprises the following steps, and the heating step is performed after the coating step:

[0062] A drying step of drying the aqueous coating composition coated on one side of the polyester film;

[0063] A stretching step of stretching the polyester film in a direction perpendicular to the longitudinal direction of the polyester film; and

[0064] The polyester film is heat treated to complete the heat setting process of crystal orientation.

[0065]

[10] The method for producing a release film according to any one of [7] to [9], wherein the liquid temperature of the aqueous coating composition in the coating step is 0° C. or higher and 40° C. or lower.

[0066] The maximum temperature of the heating step is 180° C. or higher and 250° C. or lower.

[0067]

[11] The method for producing a release film according to any one of [7] to

[10] , which is used to produce a release film for use in producing a resin sheet or a laminated ceramic capacitor.

[0068] Effects of the Invention

[0069] The release film of the present invention can improve the releasability and wettability of the release layer, thereby preventing defects from occurring in thin resin sheets, particularly ceramic green sheets.

[0070] Furthermore, the toxicity to human body and the environmental burden in the production process can be reduced. In addition, a uniform release layer can be formed without worrying about the stability of the first silicone emulsion and the second silicone emulsion contained in the aqueous coating composition being impaired. DETAILED DESCRIPTION

[0071] Since the present invention has the features described in this specification, it is possible to further solve the following problems and exhibit the effects.

[0072] In particular, the thin ceramic green sheet can be further combined with easy peelability and good wettability. In addition, compared with a coating composition containing an organic solvent as a main component, the amount of organic solvent can be greatly reduced, or the organic solvent is substantially not contained. As a result, the adverse effects on the human body caused by contact with organic solvents and inhalation of vapors, and the burden on the global environment caused by the release of organic solvent vapors into the atmosphere can be greatly reduced.

[0073] In addition, since the drying equipment for the organic solvent does not need to be explosion-proof, the energy consumption during operation can be reduced compared with the conventional manufacturing equipment. Therefore, the emission of CO2 can be reduced, and the environmental burden can be reduced.

[0074] Furthermore, according to the present invention, since aggregation and gelation of the emulsion can be suppressed, the coating uniformity is excellent, the coarse protrusions derived from the aggregates can be reduced, and the occurrence of coating defects such as cavities can be suppressed in a well-balanced manner. In addition, a release film exhibiting easy peelability can be obtained.

[0075] On this basis, according to the present invention, the reaction and solidification of the coating composition and the stretching and crystallization of the polyester film can be carried out simultaneously, and the thermal deformation of the polyester film as a substrate can be suppressed compared to the past, and the release layer can be cured at a high temperature.

[0076] In addition, since the release layer can be sufficiently cured, the release layer has excellent solvent resistance. Furthermore, for example, the force applied when peeling the ceramic green sheet can be suppressed, damage to the ceramic green sheet during peeling can be reduced, and the generation of defects can be prevented.

[0077] Furthermore, according to the present invention, when the aqueous coating composition is applied to a polyester film, coating defects such as cavities can be suppressed during the drying process, and coating defects such as uneven thickness of the release layer, generation of large protrusions, and coating omissions can be suppressed.

[0078] For example, according to the present invention, in a method of producing a release film using an in-line coating method, a release layer having excellent curing and releasability can be formed, and desired physical properties can be obtained even with wettability to ceramic slurry which was difficult to achieve conventionally.

[0079] The present invention is a release film having a release layer on at least one side of a polyester film. For example, the present invention is a release film having a polyester film and a release layer in sequence.

[0080] The release layer is a layer formed by reacting and solidifying the aqueous coating composition.

[0081] The aqueous coating composition contains 10 parts by mass or less of an organic solvent relative to 100 parts by mass of the total amount of the coating composition.

[0082] The aforementioned composition comprises:

[0083] (a) a first silicone emulsion containing at least two alkenyl groups in one molecule,

[0084] (b) a second silicone emulsion containing at least two hydrogen groups in one molecule, and

[0085] (d) a surfactant,

[0086] In the aforementioned release layer,

[0087] The adhesion energy of the surface of the release layer calculated from the rolling angle of water was 6.0 mJ / m 2 above,

[0088] The tape peeling force measured by the following method is less than 2000mN / 50mm:

[0089] The above-mentioned release film was immersed in toluene for 15 minutes and then air-dried. Then, an adhesive tape was attached to the release layer of the obtained release film and pressed with a load of 5 kg. After keeping the obtained release film with the tape at 70°C for 20 hours, T-type peeling was performed at a peeling speed of 0.3 m / min to measure the tape peeling force.

[0090] The present invention having such a structure can achieve both easy peelability and good wettability of the release layer, and can provide a thin resin sheet such as a thin ceramic green sheet without defects and with uniform thickness, and can suppress defects such as pinholes.

[0091] In addition, the present invention can achieve the following effects: In the present invention, since an aqueous coating composition containing a significantly reduced amount of organic solvent or an aqueous coating composition containing substantially no organic solvent is used compared to the past, the harmfulness to the human body and the environmental burden are reduced, and the release film can be manufactured while suppressing the generation of CO2.

[0092] Furthermore, in one embodiment, the release film of the present invention forms a release layer by applying an aqueous coating composition having a predetermined composition in an online coating method, thereby achieving both releasability and wettability. More specifically, since the silicone emulsion exhibiting thermosetting properties can be heat-cured in a relatively high temperature environment, excellent releasability is exhibited. In the online coating, since the stretching and crystallization of the substrate film and the formation of the release layer are carried out simultaneously, even at a relatively high temperature, specifically, heat of more than 180°C is applied, deformation and shrinkage of the film due to heat will not occur, and a release film with excellent planarity can be manufactured.

[0093] Furthermore, since an aqueous coating composition containing a surfactant is used, when the coating composition is applied on a polyester film to form a release layer, the release layer has no coating defects such as cavities and has excellent releasability.

[0094] Furthermore, since the stability of the silicone emulsion is increased, there is no concern about the generation of coarse protrusions or uneven thickness of the release layer due to the aggregation and gelation of the emulsion. Generally speaking, since surfactants are amphiphilic and soluble in organic solvents and water, there is a concern that the solvent resistance to organic solvents in the ceramic slurry will deteriorate and the release force will increase. However, by curing the release layer at a relatively high temperature, a release layer with a high crosslinking density and excellent solvent resistance can be obtained, and a release film with easy peelability and good wettability that was previously difficult to achieve can be manufactured.

[0095] The wettability of the release film of the present invention can be evaluated by the adhesion energy calculated from the sliding angle measured by forming a droplet on the release layer. The solvent used to form the droplet is not limited when evaluating the adhesion energy. In order to easily evaluate the amount of surfactant contained in the release layer, it is preferably calculated from the sliding angle of water. The detailed evaluation method is described below.

[0096] The peelability of the release film of the present invention can be evaluated by the tape peeling force after the release film is immersed in toluene. The peelability of the resin sheet such as the ceramic green sheet and the solvent resistance of the release layer to the organic solvent contained in the ceramic slurry coated on the release layer are important. Therefore, by using the tape peeling force after the release film is immersed in an organic solvent such as toluene, the peeling force and solvent resistance for various peeled bodies represented by the resin sheet and the ceramic green sheet can be evaluated at the same time, so it is preferred.

[0097] As a method for evaluating the excellent solvent resistance and peeling strength of the present invention, there can be mentioned a tape peeling strength test after toluene immersion treatment described below.

[0098] The tape peeling strength in the present invention can be evaluated using a commercially available adhesive tape. For example, it indicates the strength when the tape is peeled off after a release film with an adhesive tape is attached to the release layer and pressed with a load of 5 kg and kept at 70°C for 20 hours. The detailed evaluation method is described below.

[0099] As the adhesive tape, an acrylic adhesive tape can be used, and a general-purpose adhesive tape such as No. 31B manufactured by Nitto Denko Corporation can be applied.

[0100] In another aspect, the present invention provides a method for producing a release film comprising the following steps:

[0101] a coating step of coating the aqueous coating composition on at least one side of the polyester film, and

[0102] A heating step of heating the polyester film coated with the aqueous coating composition;

[0103] In the coating step, the aqueous coating composition contains 10 parts by mass or less of an organic solvent, preferably substantially no organic solvent, relative to 100 parts by mass of the total amount of the aqueous coating composition.

[0104] The aqueous coating composition contains water, a water-soluble component and / or a water-dispersible emulsion.

[0105] The surface tension of the aqueous coating composition is 40 mN / m or less.

[0106] In the production method of the present invention, in particular, by setting the production conditions when forming the release layer to a predetermined method, a release layer having excellent releasability and wettability can be formed.

[0107] For example, the molecular structure of the silicone emulsion contained in the aqueous coating composition, the molecular weight of the surfactant, the surface tension of the aqueous coating composition, the coating amount of the aqueous coating composition, the liquid temperature of the aqueous coating composition, the temperature of the heating step, etc. may be mentioned.

[0108] By producing a release film under the conditions of the present invention, the crosslinking density of the cured film of the thermosetting silicone forming the release layer is increased, the solvent resistance is improved, and easy peeling properties are exhibited. On the other hand, by leaving a surfactant in the release layer and segregating on the surface of the release layer, a release film having excellent wettability can be obtained. Details will be described later.

[0109] (Polyester film)

[0110] The polyester constituting the polyester film used as the substrate film is not particularly limited, and a polyester film obtained by film-forming a polyester commonly used as a substrate for a release film can be used. Preferably, it is a crystalline linear saturated polyester formed by an aromatic dibasic acid component and a diol component, for example, more preferably polyethylene terephthalate, polyethylene 2,6-naphthalate, polybutylene terephthalate, polytrimethylene terephthalate or a copolymer with the constituent components of these resins as the main component. In particular, it is particularly suitable to be a polyester film formed by polyethylene terephthalate. In polyethylene terephthalate, the repeating unit of ethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and a small amount of other dicarboxylic acid components and diol components can also be copolymerized. For example, from the aspect of cost, it is preferably a polyester film made only of terephthalic acid and ethylene glycol. Furthermore, known additives such as antioxidants, light stabilizers, ultraviolet absorbers, crystallizing agents, etc. may be added within a range that does not impair the effects of the release film of the present invention. The polyester film is preferably a biaxially oriented polyester film because of its high elastic modulus in both directions.

[0111] The intrinsic viscosity of the polyester film is preferably 0.50 dl / g or more and 0.70 dl / g or less, more preferably 0.52 dl / g or more and 0.62 dl / g or less. When the intrinsic viscosity is 0.50 dl / g or more, frequent fractures will not occur during the stretching process, so it is preferred. On the contrary, when the intrinsic viscosity is 0.70 dl / g or less, the cutting property when cutting into a specified product width is good, and dimensional defects will not occur, so it is preferred. In addition, the raw material pellets are preferably fully vacuum dried.

[0112] In addition, in this specification, when it is simply called "polyester film", it means the polyester film which has (laminates) the surface layer A and the surface layer B.

[0113] The method for producing the polyester film of the present invention is not particularly limited, and a conventionally commonly used method can be used. For example, the polyester film can be obtained by melting the polyester using an extruder, extruding it into a film, cooling it using a rotating cooling drum, thereby obtaining an unstretched film, and biaxially stretching the unstretched film. The biaxially stretched film can be obtained by the following method: a method of biaxially stretching a uniaxially stretched film in the longitudinal or transverse direction stepwise in the transverse direction or longitudinal direction, or a method of biaxially stretching an unstretched film in the longitudinal and transverse directions simultaneously.

[0114] In the present invention, the stretching temperature during stretching of the polyester film is preferably set to be equal to or higher than the secondary transition temperature (Tg) of the polyester. The film is preferably stretched 1 to 8 times in each of the longitudinal and transverse directions, and particularly preferably stretched 2 to 6 times.

[0115] The polyester film preferably has a thickness of 12 μm or more and 50 μm or less, more preferably 15 μm or more and 38 μm or less, and more preferably 19 μm or more and 33 μm or less. If the thickness of the film is 12 μm or more, there is no concern about deformation due to heat during film production, processing, and molding, so it is preferred. On the other hand, if the thickness of the film is 50 μm or less, the amount of film discarded after use will not be very large, which is preferred in terms of reducing environmental burden.

[0116] The polyester film substrate may be a single layer or a multilayer of two or more layers. For example, the substrate film may be a polyester film having a surface layer A substantially free of particles having a particle size of 1.0 μm or more, and a surface layer B containing particles. Preferably, the surface layer A substantially does not contain inorganic particles having a particle size of 1.0 μm or more.

[0117] In this embodiment, particles having a particle size of 1 nm or more and less than 1.0 μm may exist in the surface layer A. By making the surface layer A substantially free of particles having a particle size of 1.0 μm or more, such as inorganic particles, it is possible to reduce the transfer of particle shapes in the substrate to the resin sheet and the generation of defects.

[0118] In one embodiment, the surface layer A also does not contain particles having a particle diameter of less than 1.0 μm, thereby more effectively suppressing the transfer of the particle shape in the substrate to the resin sheet and the generation of a defect.

[0119] In one embodiment, the polyester film substrate is preferably a laminated film having a surface layer A substantially free of inorganic particles on at least one surface. This can more effectively prevent the particle shape in the substrate from being transferred to the resin sheet and causing a problem.

[0120] For example, it is preferable that the surface layer A substantially does not contain particles having a particle size of less than 1.0 μm and also substantially does not contain particles having a particle size of 1.0 μm or more.

[0121] Here, in the present invention, "substantially free of particles" means, for example, in the case of inorganic particles less than 1.0 μm, when the inorganic elements are quantified by fluorescent X-ray analysis, the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit. The reason is that even if particles are not actively added to the film, there may be contamination components from foreign matter, raw resin or dirt attached to the production line or equipment in the film manufacturing process that is peeled off and mixed into the film. In addition, "substantially free of particles with a particle size of 1.0 μm or more" means that particles with a particle size of 1.0 μm or more are not actively included.

[0122] In the case of a laminated polyester film having a multilayer structure of two or more layers, it is preferred that a surface layer B containing inorganic particles and the like is provided on the opposite side of a surface layer A containing substantially no inorganic particles.

[0123] As a stacked structure, if the layer on one side of the coating release layer is set as the A layer, the layer on the opposite side is set as the B layer, and the core layer other than these layers is set as the C layer, the layer structure in the thickness direction can be listed as: release layer / A / B or release layer / A / C / B and other stacked structures. Of course, the C layer can also be a multilayer structure. In addition, the surface layer B may not contain inorganic particles. At this time, in order to give the slipperiness for winding the film into a roll, it is preferred that a coating containing at least inorganic particles and a binder is provided on the surface layer B.

[0124] In the polyester film substrate of the present invention, the surface layer B on the opposite side of the surface where the release layer is applied is preferably provided with inorganic particles from the viewpoint of the slipperiness of the film and the ease of air discharge, and silica particles and / or calcium carbonate particles are particularly preferably used. Regarding the content of inorganic particles contained, it is preferred that the surface layer B contains inorganic particles in an amount of 5000 ppm or more and 15000 ppm or less in total.

[0125] At this time, the regional surface average roughness (Sa) of the film of surface layer B is preferably the scope of more than 1nm and less than 40nm. More preferably, the scope of more than 5nm and less than 35nm. When the total of silicon dioxide particles and / or calcium carbonate particles is more than 5000ppm and Sa is more than 1nm, when the film is rolled into a roll, air can be uniformly dispersed, and the winding posture is good and the planarity is good, thus suitable for manufacturing ultra-thin layer ceramic green sheets. In addition, when the total of silicon dioxide particles and / or calcium carbonate particles is less than 15000ppm and Sa is less than 40nm, lubricant aggregation is not easy to occur, and coarse protrusions will not be formed, so the quality is stable when manufacturing ultra-thin layer ceramic green sheets, so it is preferred.

[0126] As the particles contained in the above-mentioned B layer, in addition to silicon dioxide and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles can also be used. From the viewpoint of transparency and cost, silicon dioxide particles and / or calcium carbonate particles are more preferably used. In addition, as other usable inorganic particles, aluminum oxide-silicon dioxide composite oxide particles, hydroxyapatite particles, etc. can be listed. In addition, as heat-resistant organic particles, cross-linked polyacrylic acid particles, cross-linked polystyrene particles, benzoguanamine particles, etc. can be listed. In addition, when silicon dioxide particles are used, porous colloidal silica is preferred. When calcium carbonate particles are used, from the viewpoint of preventing the lubricant from falling off, light calcium carbonate after surface treatment with a polymer compound of a polyacrylic acid system is preferred.

[0127] The average particle size of the inorganic particles added to the surface layer B is preferably 0.1 μm or more and 2.0 μm or less, and particularly preferably 0.5 μm or more and 1.0 μm or less. If the average particle size of the inorganic particles is 0.1 μm or more, the slip property of the release film is good, which is preferred. In addition, if the average particle size is 2.0 μm or less, there is no concern about adversely affecting the smoothness of the release layer surface, so there is no concern about pinholes in the ceramic green sheet, which is preferred.

[0128] In the surface layer A as the layer on the side where the release layer is provided, it is preferred not to use recycled materials or the like in order to prevent the incorporation of inorganic particles such as lubricants from the viewpoint of reducing pinholes.

[0129] The thickness ratio of the surface layer A as a layer on the side where the release layer is provided is preferably 20% or more and 50% or less of the thickness of all layers of the substrate film. If it is 20% or more, it is not easy to be affected by particles contained in the surface layer B etc. from the inside of the film, and the regional surface average roughness Sa easily meets the above range, so it is preferred. If it is less than 50% of the thickness of all layers of the substrate film, the use ratio of recycled raw materials in the surface layer B can be increased, and the environmental burden is small, so it is preferred.

[0130] In addition, from the viewpoint of economic efficiency, 50% by mass or more and 90% by mass or less of recycled raw materials of film scraps or plastic bottles may be used in the layer other than the surface layer A (surface layer B or the intermediate layer C). In this case, the type or amount of the lubricant contained in the B layer, the particle size and the average surface roughness (Sa) of the region also preferably satisfy the above ranges.

[0131] In addition, in order to improve the adhesion of the subsequently coated release layer, etc., prevent static electricity, etc., a coating can be provided on the surface of the surface layer A and / or the surface layer B before stretching in the film forming process or after uniaxial stretching, or surface treatment can be performed.

[0132] In one mode, in order to improve the adhesion with the release layer, surface treatment can be implemented on the release layer forming surface of the aqueous coating composition, and an easy bonding layer can be set. As surface treatment, plasma treatment, corona discharge treatment, ultraviolet treatment, flame treatment and electron beam / radiation treatment etc. can be listed. As the easy bonding layer, the resin containing the same as the substrate film, the layer also containing antistatic agent, pigment, surfactant, lubricant, anti-blocking agent etc. can also be listed. When adding such adhesion improving agents of coupling agent in the aqueous coating composition, even if an easy bonding layer etc. are not set, the release layer also can have sufficient adhesion to the substrate film.

[0133] (Release layer)

[0134] In the present invention, the release layer is laminated on the surface layer A of the substrate film. In the present invention, the release layer is a layer formed by reacting and solidifying the aqueous coating composition.

[0135] The aqueous coating composition contains 10 parts by mass or less of an organic solvent relative to 100 parts by mass of the total amount of the coating composition.

[0136] The aqueous coating composition comprises:

[0137] (a) a first silicone emulsion containing at least two alkenyl groups in one molecule,

[0138] (b) a second silicone emulsion containing at least two hydrogen groups in one molecule, and

[0139] (d) Surfactant.

[0140] In the release film, the adhesion energy calculated from the rolling angle of water on the release layer is 6.0 mJ / m 2 The above, the tape peeling force measured by the following method is less than 2000mN / 50mm;

[0141] The release film was immersed in toluene for 15 minutes and then air-dried. Then, an adhesive tape was attached to the release layer of the release film with a load of 5 kg. After the release film with the tape was kept at 70°C for 20 hours, T-type peeling was performed at a peeling speed of 0.3 m / min to measure the tape peeling force.

[0142] Since the release layer has such characteristics, a release film having excellent releasability and wettability can be provided, the occurrence of defects such as pinholes in the resin sheet and the ceramic green sheet can be suppressed, and a sheet having a uniform film thickness can be formed.

[0143] More specifically, since the release layer is formed by online coating in the present invention, the release layer can be cured without damaging the planarity of the release film even in a high temperature environment of 180° C. or higher. Therefore, compared with the conventional method of forming the release layer by offline coating, a release layer with a high crosslinking density can be formed, which can have easy peeling properties.

[0144] In addition, according to the present invention, a mold release layer can be produced, which contains a surfactant soluble in water and an organic solvent and has excellent wettability when forming a sheet of a ceramic slurry, etc. Furthermore, the stability of the silicone emulsion forming the mold release layer can be improved, and a mold release film having a uniform mold release layer without coating defects can be obtained.

[0145] The aqueous coating composition for forming the release layer contains 10 parts by mass or less of an organic solvent based on 100 parts by mass of the total amount of the coating composition.

[0146] By containing an organic solvent in an amount under the above conditions, the amount of organic solvent can be significantly reduced, or substantially free of organic solvent, compared to a coating composition containing an organic solvent as a main component. As a result, the adverse effects on the human body caused by contact with organic solvents and inhalation of vapors, and the burden on the global environment caused by the release of organic solvent vapors into the atmosphere can be significantly reduced.

[0147] In one embodiment, the aqueous coating composition may include an organic solvent in an amount of 0.01 mass part or more and less than 10 mass parts, such as 0.01 mass part or more and 8 mass parts or less, 0.01 mass part or more and 5 mass parts or less, 0.01 mass part or more and 3 mass parts or less, 0.01 mass part or more and 1 mass part or less, 0.01 mass part or more and less than 1 mass part, 0.01 mass part or more and less than 0.8 mass part or less, relative to the total amount of 100 mass parts of the resin solids in the coating composition, or 0.01 mass part or more and 0.5 mass part or less.

[0148] In one embodiment, the aqueous coating composition may contain 0.01 to 0.2 parts by mass of an organic solvent, for example, 0.01 to 0.1 parts by mass. For example, the composition may contain substantially no organic solvent.

[0149] In the present invention, 100 parts by mass of the total amount of the coating composition means that, for example, the total amount of the aqueous coating composition applied to the substrate film before the completion of crystal orientation can be set to 100 parts by mass.

[0150] In the present invention, by setting the amount of the organic solvent to the above conditions, the aggregation and gelation of the first and second silicone emulsions of the present invention can be suppressed, so that the coating uniformity is excellent, the coarse protrusions derived from the aggregates can be reduced, and the occurrence of coating defects such as shrinkage cavities can be suppressed in a well-balanced manner. In addition, a release film exhibiting easy peelability can be obtained.

[0151] In addition, since the release layer can be sufficiently cured, the release layer has excellent solvent resistance. Furthermore, for example, the force applied when peeling the ceramic green sheet can be suppressed, damage to the ceramic green sheet during peeling can be reduced, and the generation of defects can be prevented.

[0152] Furthermore, according to the present invention, when the aqueous coating composition is applied to a polyester film, coating defects such as cavities can be suppressed during the drying process, and coating defects such as uneven thickness of the release layer, generation of large protrusions, and coating omissions can be suppressed.

[0153] For example, according to the present invention, in a method of producing a release film using an in-line coating method, a release layer having excellent curing and releasability can be formed, and desired physical properties can be obtained even with wettability to ceramic slurry which was difficult to achieve conventionally.

[0154] Here, in the present invention, the organic solvent includes an organic solvent that is the object of the organic solvent poisoning prevention rule as the second organic solvent (organic solvent). As the second organic solvent, for example, acetone, isopropyl alcohol, ether, cellosolve, dichlorobenzene, xylene, cresol, ethyl acetate, methyl acetate, cyclohexanol, dioxane, dimethylformamide, toluene, n-hexane, butanol, methanol, methyl ethyl ketone, etc. can be listed.

[0155] In the present invention, the composition "does not substantially contain an organic solvent" means that the composition contains the organic solvent in an amount of 0 to less than 0.01 parts by mass relative to 100 parts by mass of the total amount of the aqueous coating composition. This is because, even if the organic solvent is not actively added, it is sometimes contained in contamination components derived from foreign matter, raw material resins, additives, etc.

[0156] (a) The first silicone emulsion having at least two alkenyl groups in one molecule is obtained by emulsifying silicone containing at least two alkenyl groups in one molecule to form a water dispersion. As silicone containing at least two alkenyl groups in one molecule, any compound can be used as long as it has a siloxane bond in the main chain, preferably a polyorganosiloxane having alkenyl groups at the end and / or side chain, and more preferably polydimethylsiloxane. It is preferred to have two or more and 20 or less alkenyl groups in one molecule. When there are two or more alkenyl groups, a release layer with a high crosslinking density can be formed during thermal curing and light peeling properties can be exhibited.

[0157] Examples of the organosilicon having an alkenyl group include a structure represented by the following general formula (I).

[0158]

[0159] (In the general formula (I), R 1 may be the same or different, and are an alkenyl group having 2 to 8 carbon atoms, or a monovalent hydrocarbon group having 1 to 16 carbon atoms including an alkyl group or an aryl group, R 1 Two or more of them are alkenyl groups having 2 or more and 8 or less carbon atoms, and [SiO] b1 R represents the silicon atom bonded 1 At least one of R is an alkenyl group having 2 to 8 carbon atoms. 2 They may be the same or different and are monovalent hydrocarbon groups having 1 to 16 carbon atoms and containing an alkyl group or an aryl group. When a1+b1 is 100 mol %, a1 is 90 mol % to 100 mol %, and b1 is 0 mol % to 10 mol %.)

[0160] With [SiO] a1 R represents the silicon atom bonded 2 It can be any monovalent hydrocarbon group containing an alkyl group or an aryl group, preferably a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group, more preferably a methyl group or a phenyl group, and still more preferably a methyl group. 2 / 2 It represents the D unit structure of silicone.

[0161] With [SiO] b1 R represents the silicon atom bonded 1 Any alkenyl group having 2 to 8 carbon atoms or a monovalent hydrocarbon group containing an alkyl group or an aryl group may be used, and it is preferably [SiO] b1 R represents the silicon atom bonded 1 At least one of them is an alkenyl group having 2 to 8 carbon atoms. 1, preferably an alkenyl group having 2 to 8 carbon atoms, or a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group, more preferably a methyl group or a phenyl group, and still more preferably a methyl group.

[0162] R at both ends 1 Also with [SiO] b1 R represents the silicon atom bonded 1 Similarly, a preferred structure is an alkenyl group having 2 to 8 carbon atoms. When the terminal alkenyl group reacts with a hydrogen group, steric structural hindrance becomes small, and the peeling property is easily improved, which is particularly preferred.

[0163] As R 1 Examples of the alkenyl group having 2 to 8 carbon atoms include vinyl, allyl, butenyl, pentenyl, and hexenyl. Among these, vinyl is particularly preferred.

[0164] In [SiO] a1 With [SiO] b1 When the total amount of the constituent units of [SiO] is 100 mol%, from the viewpoint of improving the peeling property by making the hydrocarbon groups localized on the coating surface, [SiO] a1 The range of the structural units is preferably 90 mol% or more and 100 mol% or less, and a more preferred range is 92 mol% or more and 100 mol% or less.

[0165] The number average molecular weight of the organosilicon having an alkenyl group is preferably 1,000 or more and less than 30,000, and more preferably 3,000 or more and less than 15,000. When the number average molecular weight is 1,000 or more, the hydrocarbon groups are locally present on the surface of the coating film, and sufficient peeling properties are easily obtained. On the other hand, when the number average molecular weight is less than 30,000, the emulsification properties of the aqueous coating composition tend to be good, and the uniform coating properties tend to be good. It should be noted that the number average molecular weight in the present invention refers to the molecular weight calculated by 1 H NMR and 29 The peak observed by Si NMR was used to identify the siloxane unit, and the value was calculated from the integrated ratio of the peak derived from each siloxane unit.

[0166] (b) The second silicone emulsion having at least two hydrogen groups in one molecule is obtained by emulsifying silicone having at least two hydrogen groups in one molecule to form a water dispersion. As silicone having at least two hydrogen groups in one molecule, any compound can be used as long as it has a siloxane bond in the main chain, preferably a polyorganosiloxane having hydrogen groups at the end or side chain, and more preferably polydimethylsiloxane. The silicon atom at the end may also have a hydrogen group, preferably a trialkylsilane structure such as trimethylsilane. It is preferred to have more than 2 and less than 100 hydrogen groups in one molecule. By having more than 2 hydrogen groups, a release layer with a high cross-linking density can be formed during curing and exhibits light peelability.

[0167] Examples of the organosilicon having a hydrogen group include a structure represented by the following general formula (II).

[0168]

[0169] (In the general formula (II), R 3 They may be the same or different and are monovalent hydrocarbon groups having 1 to 16 carbon atoms and containing an alkyl group or an aryl group. When a2+b2 is 100 mol%, a2 is 30 mol% to 90 mol%, and b2 is 5 mol% to 70 mol%.

[0170] Hydrogen atoms (hydrogen radicals) and [SiO] a2 Represents the silicon atom bonding, R 3 It may be a monovalent hydrocarbon group containing an alkyl group or an aryl group, and is preferably a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group. 2 / 2 It represents the D unit structure of silicone.

[0171] With [SiO] b2 and R bonded to the terminal Si atom 3 It may be a monovalent hydrocarbon group containing an alkyl group or an aryl group, and is preferably a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group.

[0172] For any R 3 , it is more preferred that the carbon number of the alkyl or aryl group is a smaller number, the three-dimensional structural hindrance becomes smaller, and it becomes easier to carry out a cross-linking reaction. In addition, it is also preferred from the viewpoint of the fluidity of the coating liquid in the coating process and the uniformity of the reaction structure in the release layer. Therefore, as the alkyl group, methyl, ethyl, propyl, butyl, etc. are preferred, and as the aryl group, phenyl, tolyl, etc. are preferred.

[0173] If [SiO] a2 With [SiO] b2The total amount of the constituent units is 100 mol%, and as [SiO] a2 The range of the constituent units is preferably 30 mol% or more and 90 mol% or less, and more preferably 40 mol% or more and 80 mol% or less. a2 The constituent unit of [SiO] is 30 mol% or more, because the crosslinking reaction points become sufficient, the crosslinking density of the release layer becomes large, and the wear resistance and solvent resistance of the release layer also become good, so it is preferred. a2 It is preferred that the constituent unit of is 90 mol% or less because hydrogen groups are less likely to remain in the release layer, the amount of uncrosslinked components in the release layer is less likely to increase, and the releasability is improved.

[0174] The number average molecular weight of the hydrogen-containing silicone in the present invention is preferably 1000 to 10000, more preferably 3000 to 8000. If the number average molecular weight is 1000 or more, it becomes easy to obtain sufficient releasability. On the other hand, if the number average molecular weight is 1000 or less, the emulsification characteristics of the aqueous coating composition tend to be good, and the coating uniformity tends to be good. In addition, the cross-linking reaction tends to proceed efficiently, the residual hydrogen groups in the release layer decrease, and the releasability becomes good. It should be noted that the number average molecular weight in the present invention refers to the molecular weight calculated by 1 H NMR and 29 The peak observed by Si NMR was used to identify the siloxane unit, and the value was calculated from the integrated ratio of the peak derived from each siloxane unit.

[0175] The aqueous coating composition of the present invention preferably contains (c) a coating having SiO 4 / 2 (c) Aqueous dispersion of organosilicon containing Q units represented by SiO 4 / 2 The aqueous dispersion of the organosilicon of the Q unit represented is obtained by dispersing the organosilicon having the structure in water in the form of an emulsion, a colloid, etc. The organosilicon having the structure may be any structure as long as it is a compound having a siloxane bond in the main chain, and is preferably a polyorganosiloxane having an alkenyl group at the end and / or in the side chain. In addition, copolymers containing dialkylsiloxane units or alkylphenylsiloxane units are preferred because they exhibit peelability and are easy to adjust the amount of alkenyl groups in one molecule. The terminal silicon atom preferably has an alkenyl group, and may also be a trialkylsilane structure such as trimethylsilane.

[0176] As a SiO 4 / 2 The organosilicon of the Q unit represented by can be exemplified by the structure represented by the following formula (III).

[0177] R1 a R2 b SiO (4-a-b) / 2 ···(III)

[0178] (In formula (I), R1 is an alkenyl group having 2 to 8 carbon atoms, R2 is a monovalent saturated hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group, a is 0 to 3, b is 0 to 3, and each of them represents an integer satisfying a+b≤3.)

[0179] As the alkenyl group with 2 to 8 carbon atoms represented by R1, vinyl, allyl, butenyl, pentenyl, hexenyl, etc. can be listed, and vinyl is particularly preferred among these. In addition, as the alkyl group represented by R2, methyl, ethyl, propyl, butyl, etc. can be listed, and as the aryl group, phenyl, tolyl, etc. can be listed. From the viewpoint of reactivity with hydrogen groups, it is preferred to include an alkenyl group with 2 to 8 carbon atoms represented by R1 in (c), because the fewer the carbon atoms, the less the influence of steric hindrance, and the better the reactivity, so it is preferred, and vinyl with 2 carbon atoms is most preferred. From the viewpoint of light stripping properties, it is preferred that more than 50 mol% of the substituents of R2 are methyl groups.

[0180] Since the organosilicon with Q units can obtain a structure formed by three-dimensional expansion of siloxane bonds, the alkenyl groups in the molecule can also be spread out three-dimensionally. Therefore, by reacting the organosilicon with hydrogen groups with the alkenyl groups in the molecule, a dense cross-linked structure can be obtained, and a mold release layer with excellent solvent resistance can be obtained. Generally speaking, if the mold release layer contains SiO 2 / 2 As the ratio of the D unit represented by Q increases, the siloxane bond is more likely to acquire a helical structure. For example, in the case of polydimethylsiloxane, since the two methyl groups present in the siloxane bond are all arranged on the outside of the molecular chain, hydrophobicity is exhibited. On the other hand, if the ratio of the Q unit contained in the release layer increases, the helical structure of the siloxane bond formed by the D unit collapses, thereby reducing the hydrophobicity. Without being particularly limited by theory, by using a release layer containing silicone having Q units, it is possible to achieve both the performance of easy peelability due to the increase in crosslinking density and the reduction in hydrophobicity due to the collapse of the helical structure of the siloxane bond, that is, excellent wettability.

[0181] When the total amount of (a) the silicone contained in the first silicone emulsion having an alkenyl group, (b) the silicone contained in the second silicone emulsion having a hydrogen group, and (c) the silicone contained in the aqueous dispersion containing the silicone having a Q unit is set to 100 parts by mass, the content of the silicone contained in the aqueous dispersion containing the silicone having a Q unit in the release layer is preferably 10 to 80 parts by mass, and more preferably 20 to 70 parts by mass. If it is 10 parts by mass or more, the helical structure of the silicone containing the D unit contained in the release layer collapses due to the silicone having the Q unit, and the release layer becomes a release layer with excellent wettability, which is preferred. If it is 80 parts by mass or less, the helical structure of the silicone containing the D unit contained in the release layer does not collapse excessively due to the silicone having the Q unit, and the release layer becomes a release layer with excellent releasability, which is preferred.

[0182] The content of Si atoms contained in the Q unit is relative to that of SiO 4 / 2 The total Si atoms in the organosilicon of the Q unit represented is 0.05 mol% to 60 mol%, preferably 0.1 mol% to 55 mol%, and more preferably 1.0 mol% to 50 mol%. When the content of Si atoms contained in the Q unit is 0.05 mol% or more, a structure formed by three-dimensional expansion of siloxane bonds can be fully obtained, showing an effect of increasing crosslinking density, so it is preferred. As long as it is 60 mol% or less, there is no worry of excessive wettability causing heavy peeling, so it is preferred.

[0183] The organosilicon having Q units is preferably solid at room temperature. The organosilicon having Q units is solid because the Q unit structure in the molecule is present in large quantities in the form of continuous bonds, and the molecular skeleton is rigid and exhibits physical properties close to glass. By providing a release layer containing such an organosilicon having a rigid molecular skeleton, the elastic modulus of the release layer is improved, and when peeling off the object to be peeled off such as a ceramic green sheet, the release layer is not easily deformed, and becomes a release layer exhibiting light peelability, which is preferred.

[0184] When the total amount of (a) silicone contained in the first silicone emulsion having alkenyl groups, (b) silicone contained in the second silicone emulsion having hydrogen groups, and (c) silicone contained in the aqueous dispersion containing silicone having Q units is set to 100 parts by mass, the content of silicone contained in the second silicone emulsion having hydrogen groups in the release layer is preferably 5 to 50 parts by mass. If it is 5 parts by mass or more, the crosslinking reaction points proceed sufficiently, it becomes easy to form a dense crosslinking structure, and the stripping property is excellent, so it is preferred. If it is 50 parts by mass or less, the hydrogen groups in the release layer become less likely to remain, the activity of the surface of the release layer is less likely to increase, and the stripping property is well maintained, so it is preferred.

[0185] In one embodiment, the content of silicone contained in the (b) second silicone emulsion having a hydrogen group contained in the composition is smaller than the content of silicone contained in the (a) first silicone emulsion having an alkenyl group.

[0186] The aqueous coating composition of the present invention preferably contains at least (d) a surfactant. By containing a surfactant, the coating property when the coating composition is applied on a polyester film as a substrate film is excellent, and there is no worry about coating defects such as shrinkage cavities, so it is preferred. In addition, the stability of the emulsion present in the coating composition will not be damaged, there will be no worry about the aggregation and gelation of the coating composition being mixed into the release layer, and the generation of unevenness and uneven coating of the release layer can be suppressed, so it is preferred.

[0187] There are no particular limitations on the surfactant, and known materials can be used. In the heating process of stretching and crystallizing the substrate film, it is preferred to use a material whose volatilization amount is suppressed and remains in the release layer. By leaving the surfactant in the release layer, wettability to ceramic slurry using an organic solvent can be improved, so it is preferred.

[0188] As the surfactant, a cationic surfactant, an anionic surfactant, and a nonionic surfactant can be used appropriately, respectively. From the viewpoint of improving the stability of the emulsion, a nonionic surfactant is preferably used. For example, at least one of the alkylene oxide addition types selected from alkylene oxide adducts of higher alcohols or higher fatty acids, esters of alkylene oxide adducts of higher fatty acids and alcohols, alkylene oxide adducts of alkanolamides, alkylene oxide adducts of dehydrated sorbitan esters, and alkylene oxide adducts of higher fatty acid glycerides can be listed. As the surfactant used, the HLB value is preferably in the range of 6 to 18. Here, the HLB value is a value calculated by Griffin's calculation formula.

[0189] As the alkylene oxide, ethylene oxide, propylene oxide, and butylene oxide can be mentioned. One of these can be used, or multiple can be used. When multiple types are used, they can be in the form of block or random addition. The HLB value is preferably in the range of 8 to 18, and more preferably in the range of 10 to 15. Among these nonionic emulsifiers, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, etc. can be preferably mentioned. If a nonionic emulsifier whose HLB value deviates from this range is used as an emulsifier for the silicone water dispersion, the emulsification dispersion power and the stability of the water dispersion may be reduced.

[0190] As an example of the alkylene oxide used in the present invention, for example, a structure represented by the following formula (IV) can be illustrated.

[0191] H 2m+1 C m -O-(CH2-CH2-O) n-H(IV)

[0192] (In formula (IV), m and n are integers of 1 to 30. The number m represents the length of the alkyl chain, and the number n represents the number of moles of ethylene oxide (ethylene oxide) added.)

[0193] The larger the number of m, the longer the alkyl chain length, the better the lipophilicity, and the better the stability of the aqueous silicone emulsion, so it is preferred. In addition, the larger the number of n, the more ethylene oxide, the better the hydrophilicity, and the higher the stability of the aqueous silicone emulsion, so it is preferred. The numbers of m and n can take any value in the range of 1 to 30. The larger the number, the higher the molecular weight. In the heating and curing process of the coating composition and the stretching and crystallization process of the substrate film, the surfactant will not volatilize but remain in the release layer, so that a release film with excellent wettability can be obtained, so it is preferred.

[0194] In order to allow the surfactant to remain in the release layer, the number average molecular weight of the surfactant is preferably in the range of 200 to 2000, and more preferably in the range of 250 to 1000. In one embodiment, the number average molecular weight of the surfactant is 380 or more and 800 or less.

[0195] If the number average molecular weight is 200 or more, the surfactant will not volatilize but remain in the release layer during the heat curing process of the coating composition and the stretching and crystallization process of the substrate film, and a release film with excellent wettability can be obtained, so it is preferred. If the number average molecular weight is 2000 or less, the stability of the emulsion and the coating property of the coating composition will not be deteriorated, so it is preferred. In addition, since the surfactant segregates on the surface of the release layer during the heat curing process of the release layer, the wettability is improved, so it is preferred.

[0196] The boiling point of the surfactant is preferably above 200°C, more preferably above 230°C, and further preferably above 250°C. As long as the boiling point of the surfactant is above 200°C, the surfactant will not volatilize but remain in the release layer during the heating and curing process of the coating composition and the stretching and crystallization process of the substrate film, so it becomes a release layer with excellent wettability, so it is preferred. For example, the boiling point of the surfactant can be above 200°C and below 350°C, or above 200°C and below 320°C. By having the boiling point of the surfactant within the above range, the rapid volatilization of the surfactant can be suppressed during the process of drying and curing the release layer, and the adhesion energy calculated by the rolling angle of water can be suppressed from becoming low. In addition, the deterioration of wettability can also be suppressed.

[0197] The content of the surfactant contained in the coating composition is preferably 0.1 to 20 parts by mass, and more preferably 0.15 to 15 parts by mass, relative to the total amount of the resin solids in the coating composition. If it is 0.1 parts by mass or more, the coating property when applied on the polyester film is excellent, and the surfactant remains in the release layer, and the wettability is excellent, so it is preferred. If it is 20 parts by mass or less, there is no concern that there will be too much residual surfactant and cause heavy peeling, so it is preferred.

[0198] In this specification, the total amount of resin solids in the coating composition refers to the total amount of solids of (a) alkenyl group-containing silicone, (b) hydrogen group-containing silicone, and (c) Q unit-containing silicone added as needed.

[0199] In the present invention, the surface tension of the aqueous coating agent is preferably 10 to 40 mN / m, more preferably 10 to 35 mN / m. If it is 10 mN / m or more, it is leveled when applied on the substrate film, and has a uniform coating appearance without streaks, etc., so it is preferred. If it is 40 mN / m or less, the coating agent is easy to wet and spread on the substrate film, and the stability of the emulsion is also improved, so it is preferred. In addition, the amount of surfactant contained in the coating agent is a sufficient amount, and the surfactant remaining in the release layer after heat curing can improve the wettability of ceramic slurry, etc., so it is preferred.

[0200] (Platinum catalyst)

[0201] In the aqueous coating composition of the present invention, a platinum catalyst is required to allow the addition reaction of the organosilicon having an alkenyl group and the organosilicon having a hydrogen group. As the platinum catalyst, a known platinum catalyst can be used, for example, platinum chloride and chloroplatinic acid. Considering the dispersibility of the organosilicon, the platinum catalyst can also use 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) complex (Karstedt catalyst), and uniform dispersibility can be ensured by dispersing the organosilicon at the same time as emulsifying it.

[0202] The amount of the platinum-based catalyst is based on the amount of (a) the silicone contained in the first silicone emulsion having an alkenyl group, (b) the silicone contained in the second silicone emulsion having a hydrogen group, and (c) the silicone contained in the silicone emulsion having SiO 4 / 2The total amount of silicone contained in the aqueous dispersion of silicone of the Q unit represented is preferably contained in the range of 10 to 800 ppm by weight of the platinum element. By setting it to this range, the silicone can be sufficiently cured, and the formation of aggregates can be suppressed, and a release film with excellent smoothness can be obtained. If the weight ratio of the platinum element is 800 ppm or less, the addition reaction of the olefin group and the hydrogen group is accelerated without the worry of generating silicone aggregates, so it is preferred. The amount of platinum-based catalyst is more preferably 600 ppm or less, further preferably 500 ppm or less, and more preferably 300 ppm or less. In addition, if it is more than 10 ppm, the silicone addition reaction is efficiently carried out, the curing of the release layer becomes sufficient, and light peeling properties are exhibited, so it is preferred.

[0203] (Reaction Inhibitor)

[0204] In the aqueous coating composition of the present invention, in order to suppress the activity of the platinum-based catalyst at room temperature, a reaction inhibitor is preferably contained. The content of the reaction inhibitor is preferably 5 to 1000 ppm, more preferably 10 to 700 ppm, and preferably 20 to 500 ppm relative to the total weight of the aqueous coating composition. If it is 5 ppm or more, the effect of suppressing the activity of the platinum-based catalyst becomes sufficient, so it is preferred. If it is 1000 ppm or less, there is no concern that the reaction inhibitor volatilized during heat treatment will contaminate the inside of the oven, so it is preferred.

[0205] The aqueous coating composition of the present invention may further contain an adhesion-imparting agent, a colorant, an ultraviolet absorber, particles, and the like, within a range not impairing the subject matter of the present invention.

[0206] (Other release layer features)

[0207] The film thickness of the release layer in the present invention is preferably 0.001 to 0.2 μm, more preferably 0.005 to 0.1 μm, as a thickness after drying. If it is 0.001 μm or more, a release layer with excellent releasability can be obtained, which is preferred. If it is 0.2 μm or less, there is no need to increase the solid content concentration and coating amount of the release layer component of the aqueous coating composition, and the coating property when applied on the substrate film is excellent, which is preferred.

[0208] The tape peeling force of the release film of the present invention after toluene immersion treatment is preferably 2000mN / 50mm or less, more preferably 1500mN / 50mm or less, and further preferably 1200mN / 50mm or less. For example, it can also be 1000mN / 50mm or less. The toluene immersion treatment in the present invention refers to a process in which the release film is air-dried for 3 hours after being immersed in toluene for 15 minutes to dry the toluene attached to the release film. By evaluating the tape peeling force of the release film after toluene immersion treatment, the peeling force including the solvent resistance to the organic solvent used when molding the resin sheet, such as the ceramic green sheet, can be evaluated. If it is less than 2000mN / 50mm, it becomes a release film with excellent solvent resistance and excellent peeling property, so it is preferred. The lower the value of the tape peeling force, the better the peeling property, and in reality it is preferably more than 1mN / 50mm. If it is 1mN / 50mm or more, there is no concern that the resin sheet or ceramic green sheet after molding will float up during transportation and cause a bad condition, so it is preferred. It should be noted that the tape peeling force in the present invention can be obtained by laminating, for example, an acrylic adhesive tape on the surface of the release layer, using the No. 31B tape manufactured by Nitto Denko Corporation as an example, pressing with a load of 5kg, and sandwiching the obtained release film with the tape with a 750g glass plate. After keeping it at 70°C for 20 hours, the tape is T-peeled at a peeling speed of 0.3m / min to obtain the value.

[0209] In the release film of the present invention, the water adhesion energy calculated from the rolling angle measured by making a water drop on the release layer is preferably 6.0 mJ / m 2 More preferably, 7.0 mJ / m 2 More preferably, 8.0 mJ / m 2 Above, can also exceed 8.0mJ / m 2 , the most preferred situation is that the water drop does not roll and the adhesion energy cannot be calculated.

[0210] If the water adhesion energy is greater than 6.0mJ / m 2 , when molding thin resin sheets, ceramic green sheets, etc., shrinkage holes are less likely to occur, and defect-free and uniform thickness sheets can be obtained, so it is preferred.

[0211] If the water droplets do not roll, it can be considered that the wettability is good to the extent that the adhesion energy is too large to be calculated, so a release film on which the water droplets do not roll can also be suitably used.

[0212] In the present specification, the phrase "water droplets do not roll" means that the water droplets do not immediately roll when the release film is tilted at 90 degrees while the water droplets are attached to the release film.

[0213] Water adhesion energy is 10mJ / m 2Below, for example, 9.5 J / m 2 Below, can also be 9.0J / m 2 When the water adhesion energy is within the above range, shrinkage cavities are less likely to occur when molding a thin resin sheet, ceramic green sheet, etc., and a defect-free sheet with uniform thickness can be obtained, which is preferred.

[0214] For example, water adhesion energy is 6.0 mJ / m 2 Above and 10mJ / m 2 Below, can also be 6.0mJ / m 2 Above and 9.0mJ / m 2 the following.

[0215] (Method for producing release film)

[0216] In another embodiment of the present invention, there is provided a method for producing a release film, which comprises the following steps:

[0217] a coating step of coating the aqueous coating composition on at least one side of the polyester film, and

[0218] a heating step of heating the polyester film coated with the aqueous coating composition;

[0219] In the coating step, the aqueous coating composition contains 10 parts by mass or less of an organic solvent relative to 100 parts by mass of the total amount of the aqueous coating composition, preferably substantially contains no organic solvent but contains water and a water-soluble component and / or a water-dispersed emulsion,

[0220] The surface tension of the aqueous coating composition is 40 mN / m or less.

[0221] According to the manufacture method of the present invention, by setting the surface tension of the aqueous coating composition to less than 40mN / m, when coated on a polyester film, a uniform and defect-free release film can be obtained without coating defects such as shrinkage cavities, stripes, and uneven coating. In addition, by setting the surface tension to less than 40mN / m, the stability of the silicone emulsion in the aqueous coating composition is improved, and there is no concern that aggregates and gelled substances are mixed into the release layer and the planarity of the release film is deteriorated, so it is preferred. The surface tension is more preferably less than 35mN / m, and more preferably less than 33mN / m. It should be noted that the surface tension in the present invention represents the value of the static surface tension measured by the hanging drop method.

[0222] The surface tension of the aqueous coating composition may be 10 mN / m or more, or 15 mN / m or more. Such a condition represented by the surface tension is preferred because it is leveled when applied on a substrate film, and has a uniform coating appearance without streaks or the like.

[0223] For example, the surface tension of the aqueous coating composition may be 10 mN / m to 40 mN / m, 10 mN / m to 33 mN / m, or 15 mN / m to 33 mN / m.

[0224] The release film of the present invention can be formed by the following steps: coating an aqueous coating composition on a substrate film before the crystal orientation is completed, stretching the substrate film in at least one direction and then heat treating the substrate film to complete the crystal orientation.

[0225] The heating step in the production method of the present invention preferably further comprises the following steps:

[0226] A drying step of drying the aqueous coating composition applied to one side of the polyester film;

[0227] A stretching step of stretching the polyester film in a direction perpendicular to the longitudinal direction of the polyester film; and

[0228] The polyester film is heat treated to complete the heat setting process of crystal orientation.

[0229] For example, in the drying step of coating the aqueous coating composition on one side of a polyester film and then drying the coated film, the drying temperature may be 60°C to 140°C, for example 60°C to 130°C, or 60°C to 125°C.

[0230] By setting the temperature to 60°C or higher, there is no concern that the composition may be insufficiently dried and the film may break when the polyester film is stretched in the stretching step, so this is preferred. By setting the temperature to 140°C or lower, the composition may be prevented from being rapidly dried, and aggregation and gelation of the emulsion may be suppressed, so that coating uniformity is excellent, coarse protrusions derived from aggregates may be reduced, and the occurrence of coating defects such as shrinkage cavities may be suppressed in a well-balanced manner.

[0231] Furthermore, in the present invention, the amount of organic solvent can be greatly reduced or substantially free of organic solvent, compared with a coating composition containing an organic solvent as a main component. As a result, the adverse effects on the human body caused by contact with organic solvents and inhalation of vapors, and the burden on the global environment caused by the release of organic solvent vapors into the atmosphere can be greatly reduced.

[0232] In addition, since the drying equipment for the organic solvent does not need to be explosion-proof, the energy consumption during operation can be reduced compared with the conventional manufacturing equipment. Therefore, the emission of CO2 can also be reduced, which can reduce the environmental burden.

[0233] By having a stretching step after the drying step of drying the applied aqueous coating composition, the film temperature in the stretching step of the polyester film becomes sufficient, and there is no concern about breakage in the stretching step or uneven thickness of the release film, so it is preferred. The stretching step is preferably performed after drying the water in the aqueous coating composition, and the polyester film as the substrate is heated to a glass transition temperature or higher. The stretching temperature in the stretching step is, for example, 60°C or higher and 160°C or lower, preferably 60°C or higher and 150°C or lower, and preferably 70°C or higher and 150°C or lower from the viewpoint of stretchability.

[0234] In one embodiment, the stretching step is performed at a higher temperature than the drying step.

[0235] In the manufacturing method of the present invention, in order to impart dimensional stability and mechanical properties to the release film, it is preferred to have a heat setting process in which the stretched polyester film is heat treated to complete the crystal orientation. In order to allow the crystallization of the polyester film and the solidification of the release layer to proceed, the temperature of the heat setting process is as high as possible, but it is preferably a temperature below the melting point of the polyester. Specifically, it is preferably above 180°C and below 250°C, and more preferably above 200°C and below 240°C. If it is above 180°C, the solidification of the release layer proceeds sufficiently, and the dimensional stability and mechanical properties of the polyester film become sufficient, so it is preferred. If it is below 250°C, the crystals of the polyester film will not melt, and a release film with excellent planarity can be obtained, so it is preferred.

[0236] For example, such a heat setting step may be referred to as a heating step. The heating step may include a plurality of steps. In addition, the maximum temperature of the heating step is preferably 180° C. or higher and 250° C. or lower.

[0237] In addition, the maximum temperature in the heating step may be within the above numerical range.

[0238] In the coating process, the coating liquid temperature of the aqueous coating composition is preferably 0°C to 40°C, more preferably 5°C to 30°C. If it is 0°C or higher, there is no concern that the aqueous coating composition solidifies and the emulsion is destroyed, so it is preferred. If it is 40°C or lower, there is no concern that the emulsion in the aqueous coating composition is destroyed by heat, or that aggregates or gels are mixed in, and the generation of unevenness of the release layer and uneven coating can be suppressed, so it is preferred.

[0239] The total content of (a), (b), (c), and (d) contained in the coating composition is preferably 0.1 to 30% by mass, more preferably 0.5 to 20% by mass, and further preferably 1 to 15% by mass, relative to the total weight of the coating composition, in terms of solid content. If it is 0.1% by mass or more, the film thickness of the release layer is sufficient to show the peeling property, so it is preferred. If it is 20% by mass or less, there is no concern that the release layer becomes thick and the curing heat becomes insufficient, and the film-forming property when the substrate film is stretched is also excellent, so it is preferred.

[0240] The coating amount of the aqueous coating composition is preferably 0.1 g / m 2 Above and 10g / m 2 If the coating amount is 10g / m 2 For example, when coating is performed by gravure coating, liquid turbulence is less likely to occur at the contact portion between the film and the gravure roller, and a release layer with excellent smoothness can be obtained, so it is preferred. 2 The above is preferred because there is no concern that the uniformity of the release layer will be impaired due to coating omissions caused by shrinkage cavities or the like.

[0241] The pH of the aqueous coating composition is preferably 1 to 7, preferably 2 to 6. If the pH of the aqueous coating composition is 1 or more, there is no concern about corrosion of the tank, piping, etc. during the coating process, and there is no concern about adverse effects on the human body, so it is preferred. If the pH is 7 or less, the emulsion in the coating composition becomes stable and the coating property is excellent, so it is preferred.

[0242] As a coating method for the coating liquid, any known coating method can be applied, for example, a conventionally known method such as a gravure coating method, a roll coating method such as a reverse coating method, a rod coating method such as a wire bar, a die coating method, a spray coating method, an air knife coating method, etc. can be utilized.

[0243] In one embodiment, the production method of the present invention can provide a method for producing a release film for producing a resin sheet and a laminated ceramic capacitor.

[0244] (resin sheet)

[0245] The resin sheet of the present invention is not particularly limited as long as it is a sheet formed on the surface of the release layer opposite to the substrate. For example, it can be listed as: a resin sheet formed by curing a resin sheet molding composition containing a resin component and a crosslinking agent, a resin sheet formed by molding an organic component with film-forming properties by melt film forming and solution film forming, etc. In one embodiment, the release film of the present invention is used to manufacture a resin sheet containing an inorganic compound. As an inorganic compound, metal particles, metal oxides, minerals, etc. can be exemplified, such as calcium carbonate, silica particles, aluminum oxide particles, barium titanate particles, etc. Since the present invention has a release layer with high smoothness, even if the resin sheet contains these inorganic compounds, defects that may be caused by inorganic compounds, such as damage to the resin sheet and the problem that the resin sheet becomes difficult to peel off from the release layer, can be suppressed.

[0246] The resin component forming the resin sheet can be appropriately selected according to the application. In one embodiment, the resin sheet containing an inorganic compound is a ceramic green sheet. For example, the ceramic green sheet may contain barium titanate as an inorganic compound. In addition, the resin component may contain, for example, a polyvinyl butyral resin.

[0247] (Ceramic Green Sheets and Ceramic Capacitors)

[0248] Generally speaking, a laminated ceramic capacitor has a rectangular ceramic body. A first internal electrode and a second internal electrode are alternately arranged along the thickness direction inside the ceramic body. The first internal electrode is exposed at the first end face of the ceramic body. A first external electrode is provided on the first end face. The first internal electrode is electrically connected to the first external electrode at the first end face. The second internal electrode is exposed at the second end face of the ceramic body. A second external electrode is provided on the second end face. The second internal electrode is electrically connected to the second external electrode at the second end face.

[0249] In one embodiment, the release film of the present invention is a release film for producing a ceramic green sheet, and is used for producing such a laminated ceramic capacitor.

[0250] For example, if the release film for manufacturing ceramic green sheets of the present invention is used, the ceramic green sheets can be manufactured in the following manner. First, the release film of the present invention is used as a carrier film, and the ceramic slurry for constituting the ceramic body is applied and dried. On the ceramic green sheet after coating and drying, a conductive layer for constituting the first internal electrode or the second internal electrode is printed. A mother laminate is obtained by appropriately stacking and pressing ceramic green sheets, ceramic green sheets printed with a conductive layer for constituting the first internal electrode, and ceramic green sheets printed with a conductive layer for constituting the second internal electrode. The mother laminate is cut into a plurality of pieces to produce an unprocessed ceramic body. The ceramic body is obtained by firing the unprocessed ceramic body. Then, by forming the first external electrode and the second external electrode, a stacked ceramic capacitor can be completed.

[0251] Example

[0252] Hereinafter, the present invention will be described in further detail using examples, but the present invention is not limited to these examples. The characteristic values ​​used in the present invention were evaluated using the following methods.

[0253] (Thickness of release layer)

[0254] After the release film is cut into small triangular pieces, a Pt (platinum) layer with a thickness of 2nm is formed by coating on the surface of the release layer. The obtained sample is fixed in a multi-axis embedding capsule, embedded with epoxy resin, and sliced ​​in a direction perpendicular to the surface direction of the film using a slicer ULTRACUT-S to obtain an ultra-thin sample with a thickness of 50nm. Then, the obtained ultra-thin sample is placed on a grid and steam-stained with 2% osmic acid at 60°C for 2 hours. Using the ultra-thin sample after steam staining, the film section is observed using a transmission electron microscope LEM-2000 at an acceleration voltage of 100kV to determine the thickness of the release layer. The measurement is performed on any 10 points, and the average value of these is set as the thickness of the release layer.

[0255] (Surface tension)

[0256] The surface tension of the aqueous coating composition was measured using a contact angle meter (DM-701, fully automatic contact angle meter manufactured by Kyowa Interface Science Co., Ltd.) based on the hanging drop method. After forming the maximum amount of droplets that can be maintained without falling, the surface tension was calculated based on the ds / de method using the accompanying analysis software FAMAS. The measurement was performed 5 times in total, and the average value was used as the surface tension value.

[0257] (Liquid temperature of aqueous coating composition)

[0258] After preparing the aqueous coating composition, the liquid temperature before applying it to the polyester film was measured using a waterproof digital thermometer, and the measured value was adopted.

[0259] (Coating uniformity of release layer)

[0260] The release film wound up in a roll was unwound and cut into A4 sheets. The release layer was visually observed using a fluorescent lamp and a halogen lamp. The number of aggregated coating defects (number per A4 sheet) was compared and evaluated based on the following criteria.

[0261] ◎: No coating defects

[0262] ○: 1 to 2 coating defects

[0263] △: 3 to 5 coating defects

[0264] ×: There are 6 or more coating defects

[0265] (Ceramic Green Sheet Peelability)

[0266] The slurry composition I formed by the following materials was stirred and mixed for 10 minutes, and dispersed for 10 minutes using a bead mill with zirconia beads having a diameter of 0.5 mm to obtain a primary dispersion. Then, the slurry composition II formed by the following materials was added to the primary dispersion in a ratio of (slurry composition I): (slurry composition II) = 3.4: 1.0, and a secondary dispersion was performed for 10 minutes using a bead mill with zirconia beads having a diameter of 0.5 mm to obtain a ceramic slurry.

[0267] (Slurry composition I)

[0268]

[0269] (Slurry composition II)

[0270]

[0271]

[0272] Then, the release film sample was coated on the release surface using an applicator in such a way that the dried slurry was 2.0 μm, and dried at 60° C. for 1 minute to obtain a release film with a ceramic green sheet. The obtained release film with a ceramic green sheet was destaticized using an electrostatic eliminator (SJ-F020 manufactured by KEYENCE CORPORATION), and then peeled using a peeling tester (VPA-3 manufactured by Kyowa Interface Science Co., Ltd., with a load of 0.1 N on the load sensor) at a peeling angle of 90 degrees, a peeling temperature of 25° C., and a peeling speed of 0.3 m / min. As the peeling direction, a double-sided adhesive tape (No. 535A manufactured by Nitto Denko Corporation) was attached to the SUS plate attached to the peeling tester, and the release film was fixed thereon in a form in which the ceramic green sheet side was bonded to the double-sided tape, and peeled in a form in which the release film side was stretched. From the obtained measured values, the average value of the peeling force at a peeling distance of 20 mm to 70 mm was calculated, and this value was set as the peeling force. The measurement was performed 5 times in total, and the average value of the peeling force was used for evaluation. Based on the obtained peeling force values, the following criteria were used for evaluation.

[0273] ○: Less than 2.0mN / mm

[0274] △: Less than 5.0mN / mm

[0275] ×: 5.0mN / mm or more

[0276] (Appearance of slurry coating)

[0277] In the same manner as the above-mentioned evaluation of the releasability of the ceramic slurry, a ceramic green sheet with a thickness of 1 μm was formed on the release surface of the release film. The end surface of the ceramic green sheet formed on the release film was observed from the surface where the ceramic green sheet was laminated using an optical microscope, and visually judged according to the following criteria.

[0278] ○: The end surface of the ceramic green sheet is uniform

[0279] ×: The end surface of the ceramic green sheet is uneven

[0280] (Rolling angle of water)

[0281] The measurement was performed using a contact angle meter (DM-701, fully automatic contact angle meter manufactured by Kyowa Interface Science Co., Ltd.) at 23°C and 50% humidity. Specifically, the release film was placed on a flat glass substrate, and a drop of 7.0 μL of water was dripped on the surface of the release layer. Three seconds after the dripping, the glass plate was tilted from 0° to 90° at a tilting speed of 1.0° / second, the movement judgment distance was set to 100 dots, and the tilt angle when the droplet began to move was set as the measured value of the rolling angle. The measurement was performed 5 times in total, and the average value was used as the rolling angle.

[0282] (Adhesion Energy)

[0283] The analysis software FAMAS included in the fully automatic contact angle meter DM-701 was used to adopt the value calculated from the above-mentioned water rolling angle, liquid landing radius, droplet mass and gravitational acceleration.

[0284] (Peel strength after toluene immersion treatment)

[0285] The release film to be measured was immersed in toluene for 15 minutes, then taken out of the toluene and air-dried for 3 hours to evaporate and dry the toluene attached to the release film. Then, an adhesive tape ("No.31B tape" manufactured by Nitto Denko Corporation) was attached to the surface of the release layer of the release film, and the release film with the adhesive tape was cut into strips with a width of 25 mm and a length of 150 mm. After the cut release film with the adhesive tape was crimped with a 5kg crimping roller, the release film with the adhesive tape was clamped with a 750g glass plate and kept at 70°C for 20 hours. Then, one end of the adhesive tape was fixed, one end of the release film was supported, and the release film side was stretched at a speed of 300mm / min at 23°C, and measured by T-type peeling. The measurement was performed 3 times in total, and the value obtained by converting its average value into a 50mm width conversion value was adopted. A tensile testing machine ("AUTOGRAPH AG-X" manufactured by Shimadzu Corporation) was used for the measurement.

[0286] <Production Example 1>

[0287] (Silicone Emulsion A)

[0288] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 91% by mass of silicone oil and 9.0% by mass of polyoxyethylene alkyl ether (number average molecular weight 582, boiling point 283°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion A having a solid content of 40% by mass, wherein a1 of the above silicone oil in formula (I) was 99 mol%, b1 was 1 mol%, and the number average molecular weight was 27,000, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 9 (the structure represented by n=9 and m=12 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 200 nm.

[0289]

[0290] H 2m+1 C m -O-(CH2-CH2-O) n -H(IV)

[0291] (Silicone Emulsion B)

[0292] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 91% by mass of silicone oil and 9.0% by mass of polyoxyethylene alkyl ether (number average molecular weight 582, boiling point 283°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion B having a solid content of 40% by mass, wherein a2 of the above silicone oil in formula (II) was 50 mol%, b2 was 50 mol%, and the number average molecular weight was 5500, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 9 (the structure represented by n=9 and m=12 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 180 nm.

[0293]

[0294] Silicone emulsion A, silicone emulsion B and water were mixed in a ratio as shown in Table 1 so that the solid content concentration was 5.0% by mass to obtain an aqueous coating composition. At this time, when the total amount of silicone emulsion A and silicone emulsion B was 100, the amount of surfactant contained in the aqueous coating composition was 9.0% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a cross-linking reaction inhibitor (1-ethynylcyclohexanol) were mixed with the total weight of the aqueous coating composition.

[0295] <Production Example 2>

[0296] (Silicone Emulsion C)

[0297] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 95% by mass of silicone oil and 5.0% by mass of polyoxyethylene alkyl ether (number average molecular weight 582, boiling point 283°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion C having a solid content of 40% by mass, wherein a1 of the above silicone oil in formula (I) was 99 mol%, b1 was 1 mol%, and the number average molecular weight was 27000, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 9 (the structure represented by m=12 and n=9 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 200 nm.

[0298] Silicone emulsion C, silicone emulsion B and water were mixed in a ratio as shown in Table 1 so that the solid content concentration was 5%, thereby obtaining an aqueous coating composition. At this time, when the total amount of silicone emulsion C and silicone emulsion B was 100, the amount of surfactant contained in the aqueous coating composition was 5.2% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a cross-linking reaction inhibitor (1-ethynylcyclohexanol) were mixed with respect to the total weight of the aqueous coating composition.

[0299] <Production Examples 3 to 5>

[0300] (Silicone Emulsion D)

[0301] Using an emulsifier capable of stirring the entire container (NPLABO CO., LTD., device name "UltraPlanetary Mixer"), 90 mass % of SiO 4 / 2A raw material consisting of a silicone having a Q unit represented by 10 mass % of a polyoxyethylene alkyl ether (number average molecular weight 582, boiling point 283° C.) as a surfactant is mechanically emulsified in an aqueous medium to obtain a silicone emulsion D having a solid content of 40 mass %, wherein the polyoxyethylene alkyl ether has 12 alkyl chains and 9 ethylene oxide chains (a structure represented by m=12 and n=9 in formula (IV)). At this time, the silicone emulsion D having a solid content of 40 mass % is obtained. 4 / 2 The organosilicon of the Q unit represented by the formula (III) is shown, R1 is a vinyl group, R2 is a methyl group, and only one vinyl group is bonded to the Si atom to which the vinyl group is directly bonded. 4 / 2 Of all Si atoms in the silicone of the Q unit represented by , the content of Si atoms bonded to vinyl groups was 5 mol %, and the content of Si atoms contained in the Q unit was 40 mol %. In addition, the emulsion particle size was adjusted to an average particle size of 200 nm by adjusting the stirring speed and stirring time during emulsification.

[0302] R1 a R2 b SiO (4-a-b) / 2 ···(III)

[0303] (In formula (I), R1 is an alkenyl group having 2 to 8 carbon atoms, R2 is a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group, a is 0 to 3, b is 0 to 3, and each of them represents an integer satisfying a+b≤3.)

[0304] Silicone emulsion A, silicone emulsion B, silicone emulsion D and water were mixed in a ratio as shown in Table 1 so that the solid content concentration was 5%, thereby obtaining an aqueous coating composition. At this time, regarding the amount of surfactant contained in the aqueous coating composition, when the total amount of silicone emulsion A, silicone emulsion B and silicone emulsion D was 100, the amount of surfactant contained in Preparation Example 3 was 9.4% by mass, the amount of surfactant contained in Preparation Example 4 was 9.2% by mass, and the amount of surfactant contained in Preparation Example 5 was 9.6% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a cross-linking reaction inhibitor (1-ethynylcyclohexanol) were mixed and used relative to the total weight of the aqueous coating composition.

[0305] <Production Example 6>

[0306] (Silicone Emulsion E)

[0307] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 91% by mass of silicone oil and 9.0% by mass of polyoxyethylene alkyl ether (number average molecular weight 450, boiling point 230°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion E having a solid content of 40% by mass, wherein a1 of the above silicone oil in formula (I) was 99 mol%, b1 was 1 mol%, and the number average molecular weight was 27,000, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12, and the number of ethylene oxide chains was 6 (the structure represented by m=12 and n=6 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 200 nm.

[0308] (Silicone Emulsion F)

[0309] The preparation was carried out in the same manner as in the silicone emulsion B except that 9.0% by mass of a raw material composed of a polyoxyethylene alkyl ether (number average molecular weight 450, boiling point 230° C.) as a surfactant was used for emulsification, wherein the number of alkyl chains of the polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 6 (the structure represented by m=12 and n=6 in formula (IV)).

[0310] (Silicone Emulsion G)

[0311] The preparation was carried out in the same manner as in the silicone emulsion D except that 10% by mass of a raw material composed of a polyoxyethylene alkyl ether (number average molecular weight 450, boiling point 230° C.) as a surfactant was used for emulsification, wherein the number of alkyl chains of the polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 6 (the structure represented by m=12 and n=6 in formula (IV)).

[0312] Silicone emulsion E, silicone emulsion F, silicone emulsion G and water were mixed in a ratio as shown in Table 1 so that the solid content concentration was 5%, thereby obtaining an aqueous coating composition. At this time, when the total amount of silicone emulsion E, silicone emulsion F and silicone emulsion G was 100, the amount of surfactant contained in the aqueous coating composition was 9.4% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a cross-linking reaction inhibitor (1-ethynylcyclohexanol) were mixed with the total weight of the aqueous coating composition.

[0313] <Production Example 7>

[0314] Silicone emulsion A, silicone emulsion B, water and isopropanol were used, and mixed in a manner such that the solid content concentration was 5.0% by mass according to the ratio described in Table 1 to obtain an aqueous coating composition. At this time, 5% by mass isopropanol was used relative to the total amount of the aqueous coating composition. In addition, when the total amount of silicone emulsion A and silicone emulsion B was set to 100, the amount of surfactant contained in the aqueous coating composition was 9.0% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150ppm of a cross-linking reaction inhibitor (1-ethynyl cyclohexanol) were mixed relative to the total weight of the aqueous coating composition.

[0315] <Production Example 8>

[0316] (Silicone Emulsion H)

[0317] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 98% by mass of silicone oil and 0.1% by mass of polyoxyethylene alkyl ether (number average molecular weight 582, boiling point 283°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion H having a solid content of 40% by mass, wherein a1 of the above silicone oil in formula (I) was 99 mol%, b1 was 1 mol%, and the number average molecular weight was 27000, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 9 (a structure represented by m=12 and n=9 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 200 nm.

[0318] (Silicone Emulsion I)

[0319] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 98% by mass of silicone oil and 0.1% by mass of polyoxyethylene alkyl ether (number average molecular weight 582, boiling point 283°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion I having a solid content of 40% by mass, wherein a2 of the above silicone oil in formula (2) was 50 mol%, b2 was 50 mol%, and the number average molecular weight was 5500, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 9 (the structure represented by m=12 and n=9 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 180 nm.

[0320] Silicone emulsion H, silicone emulsion I and water were mixed in a ratio as shown in Table 1 so that the solid content concentration was 5%, thereby obtaining an aqueous coating composition. At this time, when the total amount of silicone emulsion H and silicone emulsion I was 100, the amount of surfactant contained in the aqueous coating composition was 0.1% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a cross-linking reaction inhibitor (1-ethynylcyclohexanol) were mixed with respect to the total weight of the aqueous coating composition.

[0321] <Production Example 9>

[0322] (Silicone Emulsion J)

[0323] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 91% by mass of silicone oil and 9.0% by mass of polyoxyethylene alkyl ether (number average molecular weight 362, boiling point 182°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion J having a solid content of 40% by mass, wherein a1 of the above silicone oil in formula (I) was 99 mol%, b1 was 1 mol%, and the number average molecular weight was 27,000, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 4 (the structure represented by m=12 and n=4 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 200 nm.

[0324] (Silicone Emulsion K)

[0325] Using an emulsifying device capable of stirring the entire container (manufactured by NPLABO CO., LTD., device name "UltraPlanetary Mixer"), a raw material consisting of 91% by mass of silicone oil and 9.0% by mass of polyoxyethylene alkyl ether (number average molecular weight 362, boiling point 182°C) as a surfactant was mechanically emulsified in an aqueous medium to obtain a silicone emulsion K having a solid content of 40% by mass, wherein a2 of the above silicone oil in formula (2) was 50 mol%, b2 was 50 mol%, and the number average molecular weight was 5500, and the number of alkyl chains of the above polyoxyethylene alkyl ether was 12 and the number of ethylene oxide chains was 4 (the structure represented by m=12 and n=4 in formula (IV)). In addition, by adjusting the stirring speed and stirring time during emulsification, the emulsion particle size was adjusted to an average particle size of 180 nm.

[0326] Silicone emulsion J, silicone emulsion K and water were mixed in a ratio as shown in Table 1 so that the solid content concentration was 5%, thereby obtaining an aqueous coating composition. At this time, when the total amount of silicone emulsion J and silicone emulsion K was 100, the amount of surfactant contained in the aqueous coating composition was 9.0% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a cross-linking reaction inhibitor (1-ethynylcyclohexanol) were mixed with respect to the total weight of the aqueous coating composition.

[0327] <Production Example 10>

[0328] (Silicone Emulsion L)

[0329] Using an emulsifier capable of stirring the entire container (NPLABO CO., LTD., device name "UltraPlanetary Mixer"), 90 mass % of SiO 4 / 2 A raw material consisting of a silicone having a Q unit represented by 10 mass % of a polyoxyethylene alkyl ether (number average molecular weight 362, boiling point 182° C.) as a surfactant is mechanically emulsified in an aqueous medium to obtain a silicone emulsion L having a solid content of 40 mass %, wherein the polyoxyethylene alkyl ether has 12 alkyl chains and 4 ethylene oxide chains (a structure represented by m=12 and n=4 in formula (IV)). At this time, the silicone emulsion L having a solid content of 40 mass % is obtained. 4 / 2 The organosilicon of the Q unit represented by the formula (III) is shown, R1 is a vinyl group, R2 is a methyl group, and only one vinyl group is bonded to the Si atom to which the vinyl group is directly bonded. 4 / 2 Of all Si atoms in the silicone of the Q unit represented by , the content of Si atoms bonded to vinyl groups was 5 mol %, and the content of Si atoms contained in the Q unit was 40 mol %. In addition, the emulsion particle size was adjusted to an average particle size of 200 nm by adjusting the stirring speed and stirring time during emulsification.

[0330] Silicone emulsion J, silicone emulsion K, silicone emulsion L and water were mixed in a ratio as shown in Table 1 so that the solid content concentration was 5%, thereby obtaining an aqueous coating composition. At this time, when the total amount of silicone emulsion J, silicone emulsion K and silicone emulsion L was 100, the amount of surfactant contained in the aqueous coating composition was 9.4% by mass. In addition, 0.02% by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a cross-linking reaction inhibitor (1-ethynylcyclohexanol) were mixed with respect to the total weight of the aqueous coating composition.

[0331] <Example 1>

[0332] Polyethylene terephthalate ([η] = 0.63dl / g, Tg = 78°C) containing 0.25% by mass of calcium carbonate particles with an average particle size of 0.6μm was melted by an extruder, extruded from a die through a filter with a filtration accuracy of 10μm, and cooled by a cooling drum by a conventional method to form an unstretched film. Then, after being stretched to 3.2 times at 80°C in the longitudinal direction, the aqueous coating composition obtained in Manufacturing Example 1 was uniformly applied to one surface of the polyester film by a roller coater. Then, the coated film was dried at 115°C, stretched to 4.0 times in the transverse direction at 145°C, and then heat-set at 230°C for about 10 seconds, and then rolled into a roll, thereby obtaining a roll of a release film (thickness 25μm) having a release layer shown in Table 1. The sample obtained by rolling out the release film from the obtained release film roll and cutting it into an A4 version was used to evaluate the evaluation recorded in Table 1. The amount of the aqueous coating composition applied was such that the thickness of the release layer after stretching became the thickness described in Table 1. The details of the aqueous coating composition are shown in Table 1A, and various physical properties of the film are shown in Table 1B.

[0333] <Examples 2 and 3>

[0334] A release film was obtained by the same method as in Example 1 except that the heat setting temperature was changed to the conditions described in Table 1B.

[0335] <Examples 4 to 8>

[0336] A release film was obtained by the same method as in Example 1 except that the aqueous coating compositions described in Table 1A and Table 1B were used.

[0337] <Example 9>

[0338] A release film was obtained by the same method as in Example 8 except that the heat setting temperature was changed to that described in Table 1B.

[0339] <Example 10>

[0340] A release film was obtained by the same method as in Example 1 except that the aqueous coating composition described in Table 1A was used.

[0341] <Comparative Example 1>

[0342] Using reverse gravure printing, the coating liquid of the following composition was applied to one surface of a 25 μm thick biaxially stretched polyester film (TOYOBOESTER Film E5100 manufactured by Toyobo Co., Ltd.) by an off-line coating method so that the release layer thickness after drying was 0.02 μm, and dried at 140°C for 15 seconds. After drying, an ultraviolet irradiator (Heraeus, H valve) was used on a cooling roll to irradiate with a cumulative light amount of 100 mJ / cm 2 The film was rolled up to obtain a release film roll. The release film was rolled out from the obtained release film roll and cut into an A4 size sample, and the evaluations described in Table 1B were performed.

[0343]

[0344] <Comparative Example 2>

[0345] A release film was obtained by the same method as in Example 1 except that the aqueous coating composition described in Table 1A was used.

[0346] As shown in Table 1, in Examples 1 to 10, a release film having high adhesion energy calculated by the water rolling angle, excellent wettability of the slurry, and excellent releasability of the ceramic green sheet can be obtained. In contrast, in Comparative Example 1, since an aqueous coating composition without a surfactant is used and an offline coating method is used to form a release layer, the adhesion energy calculated by the water rolling angle is low and the wettability is deteriorated. In Comparative Example 2, since the surface tension of the aqueous coating composition is high, the coating uniformity of the aqueous coating composition is poor, and shrinkage cavities are generated. Therefore, the coating appearance of the slurry is poor. In addition, the peeling force after toluene immersion treatment greatly exceeds 2000mN / 50mm, and the releasability is also poor.

[0347] <Reference Examples 1 and 2>

[0348] A release film was obtained by the same method as in Example 1 except that the aqueous coating composition described in Table 2A and the conditions in Table 2B were used. Various physical properties are shown in Table 2B.

[0349] <Reference Example 3>

[0350] The aqueous coating composition prepared in Production Example 1 was applied to one surface of a 25 μm thick biaxially stretched polyester film (TOYOBOESTER Film E5100 manufactured by Toyobo Co., Ltd.) by an off-line coating method so that the release layer thickness after drying was 0.15 μm, and dried at 140° C. for 15 seconds. After drying, the film was wound into a roll to obtain a release film.

[0351] <Reference Example 4>

[0352] A release film was obtained by the same method as in Example 1 except that the aqueous coating composition prepared in Production Example 3 was used and the heat setting temperature was set to 160° C. The surface tension of the aqueous coating composition in the coating step was 31 mJ / m 2 .

[0353] <Reference Example 5>

[0354] A release film was obtained by the same method as in Example 1 except that the aqueous coating composition prepared in Production Example 3 was used and the liquid temperature of the aqueous coating composition was heated to 50° C. The surface tension of the aqueous coating composition in the coating step was 31 mJ / m 2 .

[0355] As shown in Table 2A and Table 2B, in Reference Examples 1 and 2, the surfactant contained in the aqueous coating composition has a low number average molecular weight and a low boiling point. Therefore, it can be observed that during the drying and curing process of the release layer, the surfactant volatilizes, the adhesion energy calculated from the water sliding angle is low, and the wettability is deteriorated.

[0356] In Reference Example 3, since the water-based coating composition prepared in Manufacturing Example 1 was applied by an offline coating method, the curing temperature was low, the release layer was not cured, and adhesion occurred when it was wound into a roll. Therefore, the slurry coating appearance was poor and the peelability was also deteriorated. In Reference Example 4, the heat setting temperature was low, the release layer was not sufficiently cured, and therefore adhesion occurred when it was wound into a roll, the slurry coating appearance was poor, and the peelability was also deteriorated. In Reference Example 5, since the liquid temperature of the water-based coating composition was high, the destruction of the emulsion was observed, and shrinkage cavities were generated during the coating of the water-based coating composition, and the coating uniformity was observed to be deteriorated. As a result, it can be observed that the slurry coating appearance was poor and the peelability was also deteriorated.

[0357] The details of the aqueous coating composition are shown in Table 1A, and various physical properties related to the film are shown in Table 1B. In addition, reference examples are shown in Table 2A and Table 2B.

[0358] [Table 1A]

[0359]

[0360] [Table 1B]

[0361]

[0362] [Table 2A]

[0363]

[0364] [Table 2B]

[0365]

[0366] Industrial Applicability

[0367] The release film of the present invention has a release layer with high releasability and wettability, and therefore can suppress the occurrence of defects when a thin resin sheet, particularly a ceramic green sheet, is formed.

Claims

1. A release film comprising a polyester film and a release layer in sequence, The release layer is a layer formed by reacting and solidifying the aqueous coating composition. The aqueous coating composition contains 10 parts by mass or less of an organic solvent relative to 100 parts by mass of the total amount of the aqueous coating composition. The aqueous coating composition comprises: (a) a first silicone emulsion containing at least two alkenyl groups in one molecule, (b) a second silicone emulsion containing at least two hydrogen groups in one molecule, and (d) a surfactant, In the release layer, The adhesion energy of the surface of the release layer calculated from the rolling angle of water was 6.0 mJ / m 2 above, The tape peeling force measured by the following method is less than 2000mN / 50mm; The release film was immersed in toluene for 15 minutes and then air-dried. Then, an adhesive tape was attached to the release layer and pressed with a load of 5 kg. The release film with the tape was kept at 70°C for 20 hours and then T-peeled at a peeling speed of 0.3 m / min to measure the tape peeling force.

2. The release film according to claim 1, wherein The aqueous coating composition comprises: (c) Containing SiO 4 / 2 It represents an aqueous dispersion of a silicone with Q unit.

3. The release film according to claim 1, wherein In the aqueous coating composition, (a) the number average molecular weight of the first silicone emulsion containing at least two alkenyl groups in one molecule is 1,000 or more and less than 30,000; (b) The second silicone emulsion containing at least two hydrogen groups in one molecule has a number average molecular weight of 1,000 to 10,000.

4. The release film according to claim 1, wherein The release film is formed by the following steps: coating the aqueous coating composition on a substrate film before the crystal orientation is completed, stretching the substrate film in at least one direction and then performing a heat treatment to complete the crystal orientation of the substrate film.

5. The release film according to claim 1, wherein The polyester film has a surface layer substantially free of inorganic particles, and the release layer is formed on the surface layer.

6. The release film according to claim 1, wherein The release film is a release film for producing a laminated ceramic capacitor or a resin sheet.

7. A method for producing a release film, comprising the following steps: a coating step of coating the aqueous coating composition on at least one side of the polyester film, and a heating step of heating the polyester film coated with the aqueous coating composition, In the coating step, the aqueous coating composition contains 10 parts by mass or less of an organic solvent relative to 100 parts by mass of the total amount of the aqueous coating composition. The aqueous coating composition contains water, a water-soluble component and / or a water-dispersible emulsion. The surface tension of the aqueous coating composition is 40 mN / m or less.

8. The method for producing a release film according to claim 7, comprising the coating step of using the aqueous coating composition, The aqueous coating composition comprises: (A) a first silicone emulsion containing at least two alkenyl groups in one molecule, (B) a second silicone emulsion containing at least two hydrogen groups in one molecule, and (D) a surfactant, The surfactant has a boiling point of 200° C. or higher.

9. The method for producing a release film according to claim 7, wherein: The heating process includes the following steps, and a heating process is included after the coating process: A drying step of drying the aqueous coating composition coated on one side of the polyester film; A stretching step of stretching the polyester film in a direction perpendicular to the longitudinal direction of the polyester film; and The polyester film is heat treated to complete the heat setting process of crystal orientation.

10. The method for producing a release film according to claim 7, wherein: The liquid temperature of the aqueous coating composition in the coating step is 0° C. or higher and 40° C. or lower. The maximum temperature of the heating step is 180° C. or higher and 250° C. or lower. 11 . The method for producing a release film according to claim 7 , which is used for producing a release film for producing a resin sheet or a laminated ceramic capacitor.

Citation Information

Patent Citations

  • Silicone release coating composition and low release force emulsion silicone release coating for films and papers having cured release coating

    CN107969131A

  • Coating composition for release and silicone-releasable polyester film consisting of the same

    JP2014156560A

  • Release film

    JP2020059252A

  • Silicone release polyester film

    JP2021011081A